Chemical weathering rates and atmospheric/soil CO2 consumption of igneous and metamorphic rocks under tropical climate in southeastern Brazil - Fernandes, Alexandre Martins [UNESP]; Conceição, Fabiano Tomazini da [UNESP]; Spatti Junior, Eder Paulo [UNESP]; Sardinha, Diego de Souza; Mortatti, Jeferson (Elsevier, 2016)
Chemical weathering rates and atmosphere/soil CO2 consumption of igneous and metamorphic rocks under tropical climate in southeastern Brazil were evaluated using the chemical composition of surface waters and fresh rocks and soil (horizon C) in the Upper Sorocaba River basin. Surface water samples were collected between June/2009 and June/2010, and analyses were performed to assess pH, electrical conductivity (EC), temperature and total dissolved solids (TDS), including Na+, K+, Ca2 +, Mg2 +, Cl−, SO4 2 −, PO4 3 −, NO3 − and SiO2. Fresh rocks and C horizon samples were also collected, taking into account their geological context, abundance and spatial density, to analyze major elements and mineralogy. The concentration of TDS and dissolved cations, anions and silica increased during the dry period in relation to the wet period, and the same behavior was observed for pH, EC and temperature. After corrections of anthropogenic contributions (ca. 21 t/km2/yr) and atmospheric inputs (ca. 19 t/km2/yr), the annual flux due to chemical weathering involving the igneous and metamorphic rocks was ca. 29 t/km2/yr. The CO2 atmospheric/soil consumption in the Upper Sorocaba River basin was ca. 0.2 × 106 mol/km2/yr, and when extrapolated to the entire Mantiqueira Orogenic Belt, accounted an estimated consumption of 0.07 × 1012 mol/yr, representing 0.6% of the total CO2 consumption flux derived from global average silicate weathering. The chemical weathering rates of igneous and metamorphic rocks in the Upper Sorocaba River basin were estimated at 15 m/My, respectively. The main weathering process in this watershed was the monossialitization, with partial hydrolyses of bedrock minerals, except quartz, which was not weathered and remained in the soil profile. The annual specific flux derived from igneous and metamorphic rocks at Upper Sorocaba River basin could be compared with watersheds in tropical climates. However, this value is higher than in other North American, European, Asian and African granitoid watersheds, and lower than in montane watersheds.
Keywords: Anthropogenic and atmospheric influence; Chemical weathering; Ribeira Belt; Water-rock interactions